![](https://www1.michaeldemichele.com/img/nextpage1.png)
Suggested: 7(y+3)-2x+2)=14 4(y-2)+3(x-3)=2 by substitution method - if x=√3+1/2 find the value of 4x^3+2x^2-8x+7 - 7(y+3)-2x+2)=14 4(y-2)+3(x-3)=2 by elimination method - 2x+3y=7 (a+b+1)x+(a+2 b+2)y=4(a+b)+1 - 3x+2/7+4(x+1)/5=2/3(2x+1) - x-2 x+2-16/3x+5=3-7/2x - 7(y+3)-2x+2)=144(y-2)+3(x-3)=2 - concentric with x2+y2+2x-4y=5 radius is 7 - 3/4(7x-1)-(2x-1-x/2)=x+3/2 - expand 2x^3+7x^2+x-1 in power of x-2 - 6(2x^2-3x-2) 8(4x^2+4x+1) 1 2(2x^2+7x+3) - x=1/2-√3 find the value of x^3-2x^2-7x+5 - 2x-3y-7x+2x-y+2 - expand 2x^3+7x^2+x-6 in powers of x-2 - 7x^(2)+2x+2 Browse related:
privacy contact
Copyright 2017 bapse
bapse is powered by Google and Youtube technologies
Thank you, for using bapse.
This site was designed and coded by Michael DeMichele,
and is being used as a portfolio demonstration. View more.